DEVELOPMENT STRATEGY OF FURNITURE MSMES IN PASURUAN CITY WITH SOAR APPROACH TO IMPROVE COMPETITIVENESS AND SUSTAINABILITY - Maharani Ulya Fadhilah; Jeni Susyanti; Supriyanto (Pena Cendekia Insani, 2025)
This research aims to formulate a development strategy for furniture MSMEs in Pasuruan City using the SOAR (Strengths, Opportunities, Aspirations, Results) approach. The main problems faced are the low utilization of digital marketing and the lack of understanding of business actors on the principles of sustainability. The method used is descriptive qualitative with case studies, through observation, interviews, and documentation of MSME actors and stakeholders. The results showed that the strengths of furniture MSMEs lie in product uniqueness, local artisan skills, and availability of raw materials. Strategic opportunities include the trend of digitalization and the increasing demand for environmentally friendly local products. Business aspirations include increasing production capacity, business regeneration, and market expansion. The proposed strategies include digital marketing training, management assistance, and collaboration with educational institutions. The concrete results expected from the implementation of this strategy are an increase in sales volume by 20-30% in the medium term, increased product competitiveness through quality certification and innovative designs, and the formation of a collaborative ecosystem between furniture businesses in Pasuruan City. This research concludes that the SOAR approach is able to provide constructive and realistic strategic direction in the development of furniture MSMEs in a sustainable manner by integrating internal potential and external opportunities synergistically.